The Role of Physical Exercise in Promoting Active Living and Psychological Well-Being in Older Adults: A Literature Review - Sulistyana, Caturia Sasti; Java Perwira, Henry; Ishmaturroziqoh, Vika; Ginting, Nur Florenty Rehulina; Sabila, Nadira Silmi (International Conference on Biomedical and Sports Medicine, 2025)
Aging leads to physiological and psychological decline, reducing older adults’ quality of life. Physical exercise is recognized as a non-pharmacological intervention to maintain their health and independence. This study employed a literature review method by analyzing ten articles from 2020–2025 focused on physical exercise among individuals aged 60 and above. The findings reveal that regular physical activity improves balance, strength, mobility, and reduces insomnia, stress, and depression. Myokines released during exercise enhance anti-inflammatory and neuroprotective functions. Further analysis showed cognitive improvement, especially when combined with Brain Endurance Training, which strengthens executive function and mental resilience. Discussion of various research designs—randomized controlled trials, systematic reviews, and observational studies—supports that structured and consistent physical exercise can substitute or complement pharmacological therapy with fewer side effects. In conclusion, physical exercise is a safe, accessible, and cost-effective strategy to enhance physical, psychological, and cognitive well-being in the elderly. This study encourages the implementation of supervised exercise programs in both clinical and community settings to support healthy and active aging.